The Impact of Tourism Sector During The Covid-19 in Bali Province - Maria Regina Hilda Bunga Verena; I Made Endra Kartika Yudha; Muhammad Suprani (Masyarakat Ekonomi Syariah Bogor, 2025)
The purpose of this research is to evaluate the between the tourism industry and economic growth that occur during the Covid-19 pandemic in Bali Province. The variables used to represent Economic expansion and the tourism industry are two examples of foreign tourists, the number of domestic tourists, the number of star hotels, the number of travel agencies, while economic expansion is tracked using gross domestic product divided by population with the addition of dummy variables during the occurrence of Covid-19. Using monthly data from the 2012 to 2021 with the Error Correction Model, The findings imply that, in the near run, there is no statistically significant impact of tourism effect on economic growth. However, over time, it has a statistically significant effect and proves that the Tourism Led-Growth hypothesis is valid. The results suggest that the government can intervene the resilience of tourism actors and restore Bali's tourism image as a safe tourist destination.